2014
DOI: 10.1007/s00253-014-5847-8
|View full text |Cite
|
Sign up to set email alerts
|

New generation NMR bioreactor coupled with high-resolution NMR spectroscopy leads to novel discoveries in Moorella thermoacetica metabolic profiles

Abstract: An in situ nuclear magnetic resonance (NMR) bioreactor was developed and employed to monitor microbial metabolism under batch growth conditions in real time. We selected Moorella thermoacetica ATCC 49707 as a test case. M. thermoacetica (formerly Clostridium thermoaceticum) is a strictly anaerobic, thermophilic, acetogenic, gram-positive bacterium with potential for industrial production of chemicals. The metabolic profiles of M. thermoacetica were characterized during growth in batch mode on xylose (a compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…has increased interest in studying and engineering the bacteria not only for research but also for industrial applications [46,48]. Previous studies have indicated that, with a complex mixture of sugars, Moorella thermoacetica (M. thermoacetica) initially consumes xylose followed by fructose and then glucose, making it a unique microbial strain [49]. Batch fermentation studies operated with 20 g/L xylose showed a maximum acetic acid yield using M. thermoacetica of 0.76 g acid/g xylose [50].…”
Section: Microbes Used For Acetic Acid Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…has increased interest in studying and engineering the bacteria not only for research but also for industrial applications [46,48]. Previous studies have indicated that, with a complex mixture of sugars, Moorella thermoacetica (M. thermoacetica) initially consumes xylose followed by fructose and then glucose, making it a unique microbial strain [49]. Batch fermentation studies operated with 20 g/L xylose showed a maximum acetic acid yield using M. thermoacetica of 0.76 g acid/g xylose [50].…”
Section: Microbes Used For Acetic Acid Productionmentioning
confidence: 99%
“…These studies indicate that while the thermal degradation products of sugars and lignin obtained during thermochemical pretreatment (in this case, steam explosion) did not significantly inhibit M. thermoacetica, the primary source of inhibition was the glucose/xylose ratio and the inability of the strain to ferment other sugars such as arabinose, mannose, and galactose with high efficiency. The metabolic function of M. thermoacetica with a xylose substrate was studied using an in situ Nuclear Magnetic Resonance (NMR) bioreactor by Xue et al [49], where around 12 metabolites were identified and quantified using in situ NMR capabilities and more than 40 metabolites were identified using ex situ HR-NMR (after sample preparation to remove spectral inhibition by cells and media). Real-time NMR analysis also showed production of formate, ethanol, and methanol by M. thermoacetica using xylose as a substrate [49].…”
Section: Microbes Used For Acetic Acid Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques are certain to advance the burgeoning field of metabolomics through the added benefit of providing temporal-resolution of metabolic states. Examples of industrial RT-NMR applications include monitoring of metabolic parameters in bioreactors to optimize recombinant protein production [9], observations of xylose processing in bacteria [10], and studies of alcoholic fermentation and glycolysis in yeast [11].…”
Section: Real-time Nmr Monitoring Of Metabolic Processesmentioning
confidence: 99%
“…Since the 1990s, there have been many reports using NMR spectroscopy for the purpose of real-time reaction monitoring [ 4 , 5 , 6 , 7 , 8 , 9 ]. A primary objective has been metabolite measurement of the biological sample located directly within the NMR magnet in order to characterize metabolic function [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. In order to accurately reflect the true metabolism and not a stressed state as a result of the measurement system, the capability to maintain a sample in its natural state is essential, with additional value possible when including the potential for (bio)chemical treatment.…”
Section: Introductionmentioning
confidence: 99%